Just 2% of SARS-CoV-2-positive individuals carry 90% of the virus circulating in communities - Yang, Qing; Saldi, Tassa K; Gonzales, Patrick K; Lasda, Erika; Decker, Carolyn J; Tat, Kimngan L; Fink, Morgan R; Hager, Cole R; Davis, Jack C; Ozeroff, Christopher D; Muhlrad, Denise; Clark, Stephen K; et al. (Proceedings of the National Academy of Sciences - PNAS, 2021)
We analyze data from the fall 2020 pandemic response efforts at the University of Colorado Boulder, where more than 72,500 saliva samples were tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) using qRT-PCR. All samples were collected from individuals who reported no symptoms associated with COVID-19 on the day of collection. From these, 1,405 positive cases were identified. The distribution of viral loads within these asymptomatic individuals was indistinguishable from what has been previously observed in symptomatic individuals. Regardless of symptomatic status, ∼50% of individuals who test positive for SARS-CoV-2 seem to be in noninfectious phases of the disease, based on having low viral loads in a range from which live virus has rarely been isolated. We find that, at any given time, just 2% of individuals carry 90% of the virions circulating within communities, serving as viral "supercarriers" and possibly also superspreaders.